A three-in-one-bullet for oesophageal cancer: replication fork collapse, spindle attachment failure and enhanced radiosensitivity generated by a ruthenium(ii) metallo-intercalator. Issue 4 (23rd November 2017) - Gill, Martin R.; Jarman, Paul J.; Halder, Swagata; Walker, Michael G.; Saeed, Hiwa K.; Thomas, Jim A.; Smythe, Carl; Ramadan, Kristijan; Vallis, Katherine A.
Abstract : [Ru(phen)2 (tpphz)] 2+ simultaneously inhibits DNA replication, blocks mitosis and enhances DNA-damaging ionising radiation in oesophageal cancer cells. Abstract : Substitutionally inert ruthenium(ii ) polypyridyl complexes have been developed as DNA intercalating agents yet cellular DNA damage responses to this binding modality are largely unexplored. Here, we show the nuclear-targeting complex [Ru(phen)2 (tpphz)] 2+ (phen = 1, 10-phenanthroline, tpphz = tetrapyridophenazine) generates rapid and pronounced stalling of replication fork progression in p53-deficient human oesophageal cancer cells. In response, replication stress and double-strand break (DSB) DNA damage response (DDR) pathways are activated and cell proliferation is inhibited by growth arrest. Moreover, mitotic progression is compromised by [Ru(phen)2 (tpphz)] 2+, where the generation of metaphase chromosome spindle attachment failure results in spindle assembly checkpoint (SAC) activation. This dual mechanism of action results in preferential growth inhibition of rapidly-proliferating oesophageal cancer cells with elevated mitotic indices. In addition to these single-agent effects, [Ru(phen)2 (tpphz)] 2+ functions as a radiosensitizer with efficiency comparable to cisplatin, which occurs through a synergistic enhancement of DNA damage. These results establish that DNA replication is the target for [Ru(phen)2 (tpphz)] 2+ and provide the first experimental evidence that ruthenium-based intercalation targets multiple genome integrity pathways in cancer cells, thereby achieving enhanced selectivity compared to existing DNA-damaging agents such as cisplatin.